Exposure of the Opportunistic Marine Pathogen Photobacterium damselae subsp. damselae to Human Body Temperature Is a Stressful Condition That Shapes the Transcriptome, Viability, Cell Morphology, and Virulence - Matanza, Xosé M.; Osorio, Carlos R. (Frontiers in Microbiology, 2020)
Photobacterium damselae subsp. damselae (Pdd), an important pathogen for marine animals, is also an opportunistic human pathogen that can cause fatal necrotizing fasciitis. The regulatory changes triggered by the temperature shift experienced by this marine pathogen upon entering the human body, are completely unknown. Here we report an RNA-seq approach combined with phenotypical assays to study the response of Pdd to cultivation at 37ºC in comparison to 25ºC. We found that cultivation of a Pdd highly virulent strain for fish and mice, RM-71, at 37ºC, initially enhanced bacterial growth in comparison to 25ºC as evidenced by the increase in optical density. However, cells were found to undergo a progressive loss of viability after 6 h cultivation at 37ºC , and no viable cells could be detected from 30 h cultures at 37ºC. In contrast, at 25ºC, viable cell counts achieved the highest values at 30 h cultivation. Cells grown at 25ºC showed normal rod morphology by scanning electron microscopy analysis whereas cells grown at 37ºC exhibited chain-like structures and aberrant long shapes suggesting a defect in daughter cell separation and in septum formation. Cells grown at 37ºC also exhibited reduced tolerance to benzylpenicillin. Using a RNA-seq approach we discovered that growth at 37ºC triggered a heat-shock response, whereas genes involved in motility and virulence were repressed including iron acquisition systems, the type two secretion system, and damselysin toxin, a major virulence factor of Pdd. Human isolates did not exhibit advantage growing at 37ºC compared to fish isolates, and comparative genomics did not reveal gene markers specific of human isolates, suggesting that any Pdd genotype existing in the marine environment might potentially cause disease in humans. Altogether, these data indicate that the potential of Pdd to cause disease in humans is an accidental condition rather than a selected trait, and that human body temperature constitutes a stressful condition for Pdd. This study provides the first transcriptome profile of Pdd exposed at human body temperature, and unveils a number of candidate molecular targets for prevention and control of human infections caused by this pathogen.